Microbiome analysis revealed distinct microbial communities occupying different sized nodules in field-grown peanut - Hossain, Md Shakhawat; DeLaune, Paul B.; Gentry, Terry J. (Frontiers in Microbiology, 2023)
Legume nodulation is the powerhouse of biological nitrogen fixation (BNF) where host-specific rhizobia dominate the nodule microbiome. However, other rhizobial or non-rhizobial inhabitants can also colonize legume nodules, and it is unclear how these bacteria interact, compete or combinedly function in the nodule microbiome. Under such context, to test this hypothesis we conducted 16S-rRNA based nodule microbiome sequencing to characterize microbial communities in two distinct sized nodules from field-grown peanuts inoculated with a commercial inoculum. We found that microbial communities diverged drastically in the two types of peanut nodules (big and small). Core microbial analysis revealed that the big nodules were inhabited by Bradyrhizobium, which dominated composition (>99%) throughout the plant life cycle. Surprisingly, we observed that in addition to Bradyrhizobium, the small nodules harbored a diverse set of bacteria ( 31%) that were not present in big nodules. Notably these initially less dominant bacteria gradually dominated in small nodules during the later plant growth phases, which suggested that native microbial communities competed with the commercial inoculum in the small nodules only. Conversely, negligible or no competition was observed in the big nodules. Based on the prediction of KEGG pathway analysis for N2 and P cycling genes and the presence of diverse genera in the small nodules, we foresee great potential of future studies of these microbial communities which may be crucial for peanut growth and development and/or protecting host plants from various biotic and abiotic stresses.